HUBUNGAN AKTIFITAS OLAHRAGA DENGAN SIKAP DAN KEPUASAN HIDUP LANJUT USIA - Sufyar Mudjianto, - (2022)
Psychosocial problems in the elderly will be related to the activities carried out by the elderly including the impact of sports activities carried out regularly (regularly and measurably). Researchers feel the need to know aspects that can have a relationship with sports activities for the elderly with the basic need for satisfaction and older person's attitudes. The purpose of this study was to determine the relationship between sports activities with basic need satisfaction and older person's attitudes. The research method used is quantitative research with a correlational design. The sampling technique in this study was purposive sampling with the number of samples being 74 elderly people who met the research criteria with the age of 60 years and over. Results: (1). There is a relationship between sports activities and the level of life satisfaction of the elderly (2). There is a relationship between sports activities with the attitude of the elderly. (3) There is a difference in the satisfaction level of the elderly among the selected sports activities. (4) There are differences in the attitude of the elderly among the selected sports activities. Conclusion: There is a relationship between sports activities and the level of satisfaction and attitudes of the elderly. Keyword: Sports Activities, attitudes,basic need satisfaction in sport scale, ,Elderly.